Simple electron-electron scattering in non-equilibrium Green's function simulations. (March 2016) - Winge, David O.; Franckié, Martin; Verdozzi, Claudio; Wacker, Andreas; Pereira, Mauro F.
Abstract: In this work we include electron-electron interaction beyond Hartree-Fock level in our non-equilibrium Green's function approach by a crude form of GW through the Single Plasmon Pole Approximation. This is achieved by treating all conduction band electrons as a single effective band screening the Coulomb potential. We describe the corresponding self-energies in this scheme for a multi-subband system. In order to apply the formalism to heterostructures we discuss the screening and plasmon dispersion in both 2D and 3D systems. Results are shown for a four well quantum cascade laser with different doping concentration where comparisons to experimental findings can be made.